(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2024)
Crime is an act generally accepted to cause harm or damage to people, and its purpose is clearly defined and punished under law. According to Mayhew (2009), crime and geography are interrelated in many ways. Crime geography studies the analysis of crime, its place, and the impact of crime (including criminals) to understand how crime is influenced by society and space. This study includes the crime analysis and geographical area of Bell Tower Police Station, showing the location and time of crime from 2009 to 2019. The frequency and decline help us better understand crime and its occurrence. The main objective of this study is to improve the existing knowledge about crime and its occurrence in Ajmer city and provinces. This study aims to shed light on crime in Ajmer city, Rajasthan. According to Mayhew (2009), the crime area refers to the study of crime with the aim of gaining knowledge about the effects of crime, criminal behavior, and the interaction of crime with people and places, including criminals. Cain’s jealousy manifested itself in the killing of Habil (son of Adam and Eve), which led to the first crime in human history (Gillani, Mahmud, Rehman, & Rashid, 2008). Violence always causes unrest and distrust in society. Simply put, crime is a crime because it attempts to obtain something or break a law.